Histopathological Analysis of Breast Cancer Using Hematoxylin and Eosin Staining: Diagnostic and Prognostic Insights (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2025)
Millions of people worldwide are still impacted by breast cancer, a complicated and common health issue. This review article offers a thorough examination of the complex field of breast cancer, clarifying the wide range of risk factors that contribute to its development and investigating developments in diagnostic techniques. Millions of people worldwide are still impacted by breast cancer, a complicated and common health Numerous risk factors, including genetic predispositions such BRCA mutations, hormonal impacts, lifestyle factors, and reproductive patterns, have been found through a thorough review of recent literature. The complex aetiology of breast cancer is further influenced by environmental variables, age, and family history.New technologies like magnetic resonance imaging and molecular testing complement mammography, the mainstay of breast cancer screening, to increase the sensitivity and specificity of breast cancer diagnosis. Despite these developments, it is still difficult to guarantee that screening programs are widely accessible, especially in environments with low resources. This review concludes by highlighting the significance of comprehending the various risk factors that contribute to the development of breast cancer and the vital role that developing diagnostic techniques play in improving early detection. The critical significance that diagnostic technologies play in the early diagnosis and treatment of breast cancer is also outlined in this review.